AUSTRALIAN PSYCHIATRISTS' KNOWLEDGE, ATTITUDES, AND PRACTICE IN RELATION TO ADVANCE CARE PLANNING FOR MENTAL HEALTH TREATMENT. Issue 2 (1st June 2013) - Mountjoy, R; Silvester, W; Newton, R; Fullam, R; Mawren, D
Abstract : Background: Proposed revisions to the Victorian Mental Health Act intend to consider Advance Care Planning (ACP) in mental health treatment. No research has explored the feasibility and benefits of Psychiatric Advanced Directives (PADs) in Australia. International studies suggest that implementation of PADs can be limited by mental health clinicians' attitudes and knowledge. Aim: To establish Australian psychiatrists' knowledge, attitudes and practice regarding PADs. Methods: A national online survey of Australian psychiatrists. Results: Of 165 respondents, 56% reported low to very low knowledge of PADs and only 27% reported experience with PADs or a similar instrument. 76% of psychiatrists expressed support for the introduction of PAD legislation and 83% would be more inclined to use PADs if the law acknowledged their role as important. 79% expected that PADs will have a positive impact on mental health care, with the benefits considered to outweigh specific clinical issues such as medication refusal (54%) and limitations on patient care (64%). Discussion: Australian psychiatrists have low levels of knowledge and experience regarding PADs. A high level of general support for PAD use and legislation was expressed. Conclusion: Australian psychiatrist expressed encouraging attitudes towards the implementation and use of PADs, and further research is required to develop an effective and sustainable model of ACP for mental health care in Australia.